ヒガシ ナンキョク コウクウモウ コウソウ ノ ゲンジョウ ト カダイ - 白石, 和行; シライシ, カズユキ; Shiraishi, Kazuyuki (1995)
P(論文) 南極での国際協力による航空輸送網の構想は1970年代にSCARでかなり議論されたが実現するに至らなかった。20数年後の今日, その構想がSCALOP(南極の設営と行動に関する常置委員会)で再びよみがえった。本報告では1995年4月にワシントンDCで開かれたワークショップでの議論をもとに, 各国の南極での航空輸送網の現状をレビューし, とくに日本の南極観測隊が関係する東南極大陸における航空輸送網構想の概要と課題について解説した。 The idea of "CATSA (Cooperative Air Transportation System in Antarctica)" in 1970s revived at the SCALOP (Standing Committee on Antarctic Logistics and Operations) Workshop in Washington, D. C., April 1995. This report describes a short historical background and the present status of the idea with some information on the present and recent air transportation by various countries on the basis of the discussion at the workshop. In particular, the East Antarctic Air Network is discussed with some critical points to be solved. departmental bulletin paper